PENERAPAN MODEL INKUIRI TERBIMBING DENGAN PENDEKATAN SELF REGULATED LEARNING UNTUK MENINGKATKAN DISPOSISI KREATIF DAN KETERAMPILAN BERPIKIR KREATIF SISWA PADA MATA PELAJARAN BIOLOGI - Shabilla Ramadhita Algiani; I Putu Artayasa; AA Sukarso; Agus Ramdani (Jurnal Penelitian Pendidikan IPA, 2023)
Given the importance of globalization and the need to train students' thinking skills and broad knowledge to prepare them to face the demands of the 21st century work, education from the start needs to look more critically at educational practices and learning methods that should be directed. This study seeks to examine the effect of applying the guided inquiry model with the Self Regulated Learning approach to students' creative dispositions and creative thinking skills in high school biology learning. To achieve this goal, a sample of 70 students at one of the State Senior High Schools in Mataram, NTB. Subjects were purposively grouped into the experimental class, namely learning using the Guided Inquiry Model with the Self Regulated Learning (IT-SRL) Approach and the control class using the Ordinary Guided Inquiry (IT) model. Data on students' creative dispositions were obtained from a creative disposition questionnaire while data on students' creative thinking skills were obtained from tests of creative thinking skills which were compiled based on indicators of creative thinking skills. Hypothesis testing in this study uses. The results of the ANCOVA test showed that students who were taught using the guided inquiry model using the self-regulated learning (IT-SRL) approach had better creative dispositions and creative thinking skills than students who were taught using the inquiry method (IT).